BRAND ACTIVISM IN POLARIZED SOCIETIES: A STAKEHOLDER THEORY PERSPECTIVE ON RISKS, COMMUNICATION, AND LONG-TERM EQUITY - Raja Risnanda Putra; Lukmanul Hakim; Tibrani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Brand activism has emerged as a prominent strategy in contemporary marketing as organizations increasingly engage with social, political, and environmental issues. In highly polarized societies, however, such actions present both opportunities and risks, creating uncertainty regarding stakeholder responses and long-term brand outcomes. This study examines brand activism through a stakeholder theory perspective, focusing on risks, communication strategies, and implications for long-term brand equity. Using a narrative literature review and conceptual analysis, the study synthesizes insights from academic research, case studies, and industry reports related to stakeholder dynamics, societal polarization, and brand communication. The findings reveal that stakeholder responses are highly fragmented, with supportive groups enhancing loyalty and opposing groups generating backlash and reputational risk. Effective communication—characterized by authenticity, clarity, and responsiveness—emerges as a critical factor in mitigating risks and shaping perceptions. The study also highlights the trade-off between short-term negative reactions and potential long-term gains in trust, loyalty, and brand equity. A conceptual framework is proposed to explain how brand activism influences outcomes through mediating and moderating factors. The study concludes that successful brand activism requires strategic alignment, stakeholder awareness, and proactive communication to navigate polarized environments and sustain long-term value.